Analisis dampak perubahan iklim terhadap kualitas air tanah di indonesia - Ramadani, Nia (Maliki Interdisciplinary Journal, 2025)
Climate change in Indonesia has a significant impact on groundwater quality, including changes in rainfall patterns and increasing temperatures. This can cause pollution and decreased availability of clean water, which has the potential to threaten public health and ecosystems. This study aims to analyze climate change on groundwater quality in various regions of Indonesia. The methods used include literature reviews, climate and hydrological data analysis, and case studies in various regions experiencing declining groundwater quality. The results of the analysis show that increasing temperatures, changes in rainfall patterns, and sea level rise directly and indirectly affect the physical and chemical parameters of groundwater, such as increased concentrations of heavy metals, salinity contamination, and changes in pH.